2019
DOI: 10.3390/ijms20030782
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Transformation of the Cellular Toxin INT (2-(4-Iodophenyl)-3-(4-Nitrophenyl)-5-(Phenyl) Tetrazolium Chloride) as an Indicator of Prior Respiratory Activity in Aquatic Bacteria

Abstract: In the ocean, the prokaryote respiration rates dominate the oxidation of organics, but the measurements may be biased due to pre-incubation size filtration and long incubation times. To overcome these difficulties, proxies for microbial respiration rates have been proposed, such as the in vitro and in vivo estimation of electron transport system rates (ETS) based on the reduction of tetrazolium salts. INT (2-(4-Iodophenyl)-3-(4-Nitrophenyl)-5-(Phenyl) Tetrazolium Chloride) is the most commonly applied tetrazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
(52 reference statements)
0
5
1
Order By: Relevance
“…Therefore, reinforcing previous work [6], the results show that INT reduction can be used as a proxy for plankton respiration when incubated for specifically determined short time periods. However, we cannot recommend a particular maximum incubation time and do not support the idea of a constant incubation time for the INT reduction method with natural plankton or eukaryotic cultures as other authors have suggested for prokaryotes [11]. The maximum incubation time (determined as the time after which INT had a negative effect on oxygen consumption) was not related to cell abundance or by implication to biomass alone.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Therefore, reinforcing previous work [6], the results show that INT reduction can be used as a proxy for plankton respiration when incubated for specifically determined short time periods. However, we cannot recommend a particular maximum incubation time and do not support the idea of a constant incubation time for the INT reduction method with natural plankton or eukaryotic cultures as other authors have suggested for prokaryotes [11]. The maximum incubation time (determined as the time after which INT had a negative effect on oxygen consumption) was not related to cell abundance or by implication to biomass alone.…”
Section: Discussioncontrasting
confidence: 59%
“…The increased sensitivity of this measurement, allowing less disruption of the sample and shorter incubation times (from minutes to hours) compared to the traditional Winkler titration method (usually 24 hours), has enabled improved understanding of the spatial and temporal variability of plankton respiration [8] as well as the apportionment of total plankton respiration to different size classes [810]. However, despite validation of INT reduction (INT R ) as a proxy for plankton respiration [6], the method remains controversial [11, 12]. Several researchers have shown that the reduction of soluble tetrazolium salts can have a toxic effect on cells, potentially due to formazan production inhibiting the electron transport system [13], leading to a reduction in metabolic activity [5, 12].…”
Section: Introductionmentioning
confidence: 99%
“…This can be used to determine the respective proportion of active and inactive cells in various samples by comparison to microscopy count, for example (Dufour and Colon, 1992;Haglund et al, 2002;Bartosch et al, 2003). Similarly, studies have shown that the production of formazan per cell increases following an increase in growth rate (Villegas-Mendoza et al, 2019). On the contrary, at a later stage of batch culture (late stationary phase), where most cells are not growing anymore, staining of such cells by tetrazolium was poor (Fukui and Takii, 1989).…”
Section: Redox Assays Tetrazolium Saltsmentioning
confidence: 99%
“…The enzymatic electron transport system drives oxidative phosphorylation. It has frequently been used as a proxy for respiration (Minutoli and Guglielmo 2009; Villegas‐Mendoza et al 2019). In vivo electron transport system activity was measured at in situ temperature based on tetrazolium salt 2‐para(iodo‐phenyl)‐3(nitrophenyl)‐5(phenyl)tetrazolium chloride (INT) reduction rate following the protocol of Martinez‐Garcia et al (2009).…”
Section: Methodsmentioning
confidence: 99%